Новітні методи 3D-реконструкції обличчя на основі фотографічних зображень в задачах пластичної хірургії - Бажан, О. В.; Тимкович, М. Ю. (ХНУРЕ, 2020)
The work is devoted to the analysis of modern approaches of three-dimensional reconstruction of the face, for the problems of plastic surgery. The study shows the most up-to-date methods of three-dimensional reconstruction of a face by one photo and their structure. A further step in the study is the use of the above methods in facial reconstruction.
Keywords: фотографічне зображення; обличчя; пластична хірургія; 3D реконструкція